THE RESPONSE OF PRECIPITATION TO OROGRPAHY IN SIMULATIONS OF FUTURE CLIMATE - Rögnvaldsson, Ólafur; University of Bergen, Norway, Institute for Meteorological Research, Iceland, Icelandic Meteorological Office, Bústaðavegur 9, IS–150, Iceland; or@os.is; Ólafsson, Haraldur; Institute for Meteorological Research, Iceland, Icelandic Meteorological Office, Bústaðavegur 9, IS–150, Iceland, University of Iceland, Iceland (Croatian meteorological society; info@meteohmd.hr, 2005)
Abstract: Precipitation pattern in Iceland in relatively high–resolution simulations of the future climate is investigated. In the winter and in the autumn ther is much greater increase in precipitation over the mountain slopes than elswhere, indicating that a future climate may feature a topographic precipitation gradient that is different than in the current climate. The results are an encouragement to go to even higher resolutions in climate simulations, rather than to apply the so–called delta change to estimate changes in precipitation climate.